Menilai Kinerja Keuangan Dengan Analisis Rasio Likuiditas Pada PT Bank Negara Indonesia Pada Tahun 2019-2020 - Nur Anis Machfudloh; Afrixson Leonardo Alexzander; Renny Oktafia (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
Banking is an industry in the financial sector which can be interpreted as the backbone of the economic and financial system in Indonesia as well as being a channel of funds to the community in order to achieve equitable development, and to assess the financial performance of a bank you can look at its financial reports as an indicator. Financial reports are transactions in and out of banking with monetary and economic value which are recorded in a report. The aim of this research is to analyze the increase or decrease in Bank Negara Indonesia's financial reports for the 2020 period using descriptive and quantitative methods using the liquidity ratio method as a measuring tool. The results of research on liquidity ratios at Bank BNI for the 2019-2020 period show that BNI's CR calculations in 2019 and 2020 are below the ideal standard (100% or 1:1), but not below the minimum standard (80% or 0.8 :1)2. In 2019 and 2020, BNI's CR value cannot be considered to have a poor level of liquidity. BNI's QR value in 2019 was 10.0% and in 2020 it was 10.1%. Ideally, QR is 100% or 1:1, and the minimum is 80% or 0.8:1. If the QR is below the predetermined standard, then the level of liquidity is considered to be poor. In 2019, BNI's LDR value was 89.0%, which is below the ideal standard (94.75%). In 2020, BNI's LDR value was 79.5%, which is lower than the minimum standard (93.75% - 97.50%) and the ideal standard (94.75%). Based on this data, BNI's liquidity level in 2019 and 2020 is limited and cannot be considered good.